(untitled) (Szociológiai Szemle, 2024)
In the system-theory of Luhmann the separation of each sub-system is effected by the symbolically generalized media of the respective sub-system. This view is called in question by Béla Pokol who introduced the concept of „double rationality”, stressing that the independence of the social sub-systems requires not only their own media, but also the presence of the financial medium. Consequently, he thinks that the independence of each sub-system (such as science, arts, etc.) can be secured if the activities within these spheres are financed by the market. In this paper, trying to assess this standpoint, we compare the original theory of Luhmann with the „double rationality” thesis of Pokol, utilizing the concept of Polányi regarding the „dual economy”. According to our findings it is not the sphere of economy itself, but rather the separation of the economic and political sub-systems that serves as the basis for the process whereby the other social sub-systems become gradually independent. These two sub-systems have crucial significance in the formation and preservation of the structure of modern society. Financing each separated — non-economic and non-politic sub-system — poses such a dilemma that cannot be solved on the theoretical basis of those macro-sociological concepts which have been elaborated to depict the differentiation of the social sub-systems: the answers concerning the problems of financing cannot be deducted with constraint from the network of macro-sociological concepts.